2012
DOI: 10.1038/bjc.2012.261
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin plus paclitaxel and maintenance of bevacizumab on tumour progression, dissemination, and survival of ovarian carcinoma xenograft models

Abstract: Background:Bevacizumab is being incorporated as first-line therapy with standard-of-care chemotherapy on epithelial ovarian carcinoma (EOC). We investigated bevacizumab combined with chemotherapy on tumour progression and mouse survival in EOC xenograft models.Methods:Bevacizumab was administered concomitantly with cisplatin plus paclitaxel (DDP+PTX), continued after induction (maintenance) or started after chemotherapy. The effect on tumour progression was monitored by bioluminescence imaging (BLI) (1A9-luc x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 46 publications
3
32
0
Order By: Relevance
“…However, the overall survival benefits of those antiangiogenic drugs have been modest: often the response to therapy is short lasting, and patients become refractory or escape treatment (8,36). Recent preclinical studies have even shown increased invasion and metastasis in mouse tumor models treated with certain angiogenesis inhibitors (16)(17)(18)(19)(20)(21)(22). Less clear is whether the resistance/escape to therapy using angiogenesis inhibitors, with accelerated disease progression or increased mortality, also happens in patients.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the overall survival benefits of those antiangiogenic drugs have been modest: often the response to therapy is short lasting, and patients become refractory or escape treatment (8,36). Recent preclinical studies have even shown increased invasion and metastasis in mouse tumor models treated with certain angiogenesis inhibitors (16)(17)(18)(19)(20)(21)(22). Less clear is whether the resistance/escape to therapy using angiogenesis inhibitors, with accelerated disease progression or increased mortality, also happens in patients.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, antiangiogenic therapy was extremely effective on the primary tumor and metastasis, improving survival (13)(14)(15). However, surprisingly, recent studies reported that treatment of tumor-bearing mice, mainly with anti-VEGF/VEGFR-related compounds, increased tumor invasiveness and metastasis (16)(17)(18)(19)(20)(21)(22). Clinical data on the effect of antiangiogenesis in general, or anti-VEGF therapy, on malignant progression are lacking and widely debated.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations